On the Need for a New Psychotherapy Research Paradigm Comment on Westen, Novotny and Thompson Brenner (2004). (Articles]. - Goldfried, Marvin R.
Basic, Process and outcome research have the potential to inform clinical practice, however, as D. Westen, C. M. Novotny and H. Thompson -Brenner (2004) observed in their timely analysis, the current dominant paradigm for psychotherapy outcome research-the randomized. clinical trial-is not fulfilling this potential. The fields reliance on the medical model and manual-based intervention has contributed to the gap between research and clinical practice greater collaborations between practitioners and researchers and focus on therapeutic principles rather than treatment packages, and systematic changes on how scholarly efforts are reinforced are needed to shift the current research paradigm-- (from the author